Paste-processed ultra-high molecular weight polyethylene expanded into high density articles
The method of pasting and stretching UHMWPE polymers addresses the inefficiencies of conventional processing by producing high-density films with high strength and low permeability, achieving superior mechanical and optical properties.
Patent Information
- Application Number
- JP2024535861
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-16
- Filing Date
- 2022-12-08
- Publication Date
- 2024-12-26
- Estimated Expiration
- 2042-12-08
AI Technical Summary
Conventional processes for processing ultra-high molecular weight polyethylene (UHMWPE) polymers are hindered by high solvent usage, high viscosity, and are often expensive or time-consuming, lacking in producing high-strength films with excellent barrier properties, optical uniformity, and transparency.
A method involving pasting UHMWPE polymers with a lubricant, forming a tape, removing the lubricant to create a dry porous tape, and stretching it in multiple directions at temperatures above the melting point to form high-density UHMWPE films with distinct endotherms, achieving high tensile strength and low gas permeability.
The method produces UHMWPE films with high tensile strength, low haze, and excellent transparency, along with low gas and water vapor permeability, suitable for various applications.
Smart Images

Figure 2024546933000001_ABST
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of Provisional Application No. 63 / 290,154, filed December 16, 2021, which is incorporated herein by reference in its entirety for all purposes.
[0002] Field The present disclosure relates generally to pasted ultra-high molecular weight polyethylene (UHMWPE) polymers, and more specifically to a method for forming high density films from highly crystalline ultra-high molecular weight polyethylene polymers. [Background technology]
[0003] background Ultra-high molecular weight polyethylene is well known in the art. Articles made from ultra-high molecular weight polyethylene have properties such as toughness, impact strength, abrasion resistance, low coefficient of friction, gamma resistance, and resistance to attack by solvents and corrosive chemicals. Due to its favorable properties, ultra-high molecular weight polyethylene is utilized in a variety of applications, such as load-bearing components of joint prostheses, vibration damping pads, hydraulic cylinders, skis, ski poles, goggle frames, protective helmets, sports equipment including, but not limited to, climbing equipment, and specialty aerospace applications.
[0004] UHMWPE polymer can be processed by compression molding, ram extrusion, gel spinning and sintering. However, some conventional processes have one or more undesirable characteristics or properties, such as requiring high levels of solvents and / or being expensive or time-consuming to process due to the high viscosity of UHMWPE polymer. Therefore, there is a need in the art for paste processing to make UHMWPE intermediates (e.g., tapes or films) that are then processed into high density films with excellent mechanical properties and optional properties, such as high strength, excellent barrier properties, optical uniformity, low haze and transparency. Summary of the Invention
[0005] Abstract Provided herein are high density films formed from pasted ultra-high molecular weight polyethylene (UHMWPE) polymers, and methods for forming these films from highly crystalline ultra-high molecular weight polyethylene polymers.
[0006] According to a first embodiment ("Embodiment 1"), there is provided a high density ultra-high molecular weight polyethylene (UHMWPE) film having a first endotherm at about 135°C to about 143°C, a second endotherm at about 145°C to about 155°C, and a total light transmittance of at least about 90% measured from 360 nm to 780 nm.
[0007] Embodiment 2 is the high density UHMWPE film of embodiment 1, wherein the UHMWPE film has a machine direction (MD) matrix tensile strength of at least 200 MPa.
[0008] Embodiment 3 is the high density UHMWPE film of embodiment 1 or 2, wherein the UHMWPE film has a matrix tensile strength in the transverse direction (TD) of at least 400 MPa.
[0009] Embodiment 4 is the high density UHMWPE film of any of Embodiments 1-3, having a matrix tensile strength MD:TD ratio of about 1:5 to about 5:1.
[0010] Embodiment 5 is the high density UHMWPE film of any of embodiments 1-4, wherein the UHMWPE film has a CO2 permeability or O2 permeability or N2 permeability of less than 10 barrels.
[0011] Embodiment 6 is the high-density UHMWPE film of any of Embodiments 1 to 5, wherein the thickness of the UHMWPE film is 0.0005 mm to 1 mm.
[0012] Embodiment 7 is the high density UHMWPE film of any of embodiments 1 to 6, wherein the high density UHMWPE film is formed from a UHMWPE polymer having a molecular weight of about 2,000,000 g / mol to about 10,000,000 g / mol and a melting enthalpy of greater than 190 J / g.
[0013] Embodiment 8 is a composite material including the high density UHMWPE film of any of embodiments 1-7.
[0014] Embodiment 9 is an article comprising the high density UHMWPE film of any of embodiments 1-8.
[0015] According to a tenth embodiment ("Embodiment 10"), there is provided a method of forming a high density UHMWPE film comprising forming a dried porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g, compressing the dried porous UHMWPE tape at a temperature below the melting temperature of the UHMWPE polymer, and stretching the UHMWPE tape in at least two directions at a temperature above the melting temperature of the UHMWPE polymer to form a high density UHMWPE film. The high density UHMWPE film comprises a first detectable endotherm at about 135°C to about 143°C and a second detectable endotherm at about 145°C to about 155°C.
[0016] Embodiment 11 is the method of embodiment 10, wherein the high density UHMWPE film has a total light transmittance measured from 250 nm to 800 nm of at least about 98%.
[0017] Embodiment 12 is the method of embodiment 10 or 11, wherein the forming step includes providing a paste including a UHMWPE polymer as a powder and a lubricant, forming the paste into a tape, removing the lubricant to form a dried porous UHMWPE tape, and stretching the tape to form a high density UHMWPE film.
[0018] Embodiment 13 is the method of embodiments 10-12, wherein the step of stretching the compressed UHMWPE tape is carried out at a temperature of 140° C. to 170° C. and at a rate of about 0.1% to 20,000% / sec.
[0019] In a fourteenth embodiment, the high density UHMWPE film further comprises a machine direction matrix tensile strength / transverse direction matrix tensile strength ratio of about 1:5 to about 5:1, a matrix tensile strength of at least 500×500 (MD×TD) MPa, a CO, O, or N permeability of 0.01 to 10 barrels, and a water vapor permeability of 0.02 g-mm / m 2 14. The method of embodiments 10 to 13, wherein the daily intake is less than 100 mg / day.
[0020] According to a fifteenth embodiment ("Embodiment 15"), there is provided a method of forming a high density UHMWPE film, the method comprising forming a dried porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g, and stretching the dried porous UHMWPE tape in at least two directions at a temperature above the melting temperature of the UHMWPE polymer to form a high density UHMWPE film, wherein the high density UHMWPE film has a first detectable endotherm at about 135°C to about 143°C and a second detectable endotherm at about 145°C to about 155°C.
[0021] Embodiment 16 is the method of embodiment 15, wherein the forming step includes providing a paste including a UHMWPE polymer as a powder and a lubricant, forming the paste into a tape, removing the lubricant to form a dry porous UHMWPE tape, and stretching the tape to form a high density UHMWPE film.
[0022] Embodiment 17 is the method of embodiment 15 or 16, wherein the step of stretching the dried UHMWPE tape is carried out at a temperature of 140° C. to 170° C. and at a rate of about 0.1% to 20,000% / sec.
[0023] Embodiment 18 is the method of embodiments 15-17, wherein the high density UHMWPE film further has a machine direction matrix tensile strength / transverse direction matrix tensile strength ratio of about 1:5 to about 5:1, a matrix tensile strength of at least 200×200 (MD×TD) MPa, and a CO, O, or N permeability of 0.01 to 10 barrels.
[0024] According to a nineteenth embodiment ("Embodiment 19"), there is provided a method of forming a high density UHMWPE film, comprising: (a) forming a porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g, wherein the porous UHMWPE tape, (b) expanding (expanding, expanding, stretching or foaming) the porous UHMWPE tape at a temperature below the melting temperature of the porous UHMWPE tape to form a porous membrane; and (c) compressing the porous UHMWPE membrane at a pressure of at least 1 MPa to form a high density UHMWPE film with a first detectable endotherm of about 135°C to about 143°C and a second detectable endotherm of about 145°C to about 155°C.
[0025] Embodiment 20 is the method of embodiment 19, further comprising: (d) stretching the high density UHMWPE film at a temperature above the melting temperature of the UHMWPE polymer.
[0026] Embodiment 21 is the method of embodiment 19 or 20, wherein the stretching and compressing steps are performed simultaneously.
[0027] Embodiment 22 is the method of embodiments 19-21, wherein the stretching step after compression is carried out at a temperature of about 140°C to about 170°C.
[0028] Embodiment 23 is the method of embodiments 19-22, wherein the high density UHMWPE film further has a machine direction matrix tensile strength / transverse direction matrix tensile strength ratio of about 1:5 to about 5:1, a matrix tensile strength of at least 200×200 (MD×TD) MPa, and a water vapor permeability coefficient of less than 0.21 g-mm / m2 / day.
[0029] Embodiment 24 is the method of embodiments 10-23, wherein the stretching step comprises biaxial stretching or radial stretching.
[0030] The foregoing embodiments are just embodiments and should not be construed as limiting or narrowing the scope of any of the inventive concepts otherwise provided by this disclosure. While multiple examples are disclosed, still other embodiments will become apparent to those skilled in the art from the following detailed description, which shows and describes illustrative examples. Thus, the drawings and detailed description are to be regarded as illustrative in nature and not restrictive. [Brief description of the drawings]
[0031] BRIEF DESCRIPTION OF THE DRAWINGS Advantages of the present invention will become apparent upon consideration of the following detailed disclosure of the invention, particularly when considered in conjunction with the accompanying drawings.
[0032] [Figure 1] FIG. 1 is a differential scanning calorimetry (DSC) thermogram of the UHMWPE powder of all the examples described herein, showing an enthalpy of fusion of 232.9 J / g.
[0033] [Diagram 2] FIG. 2 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the UHMWPE high density film of Example 1.
[0034] [Diagram 3] FIG. 3 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the UHMWPE high density film of Example 2.
[0035] [Figure 4] FIG. 4 is a differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the UHMWPE high density film of Example 3a.
[0036] [Diagram 5] FIG. 5 is a plot of the comparative permeability to nitrogen, oxygen and carbon dioxide gases of the UHMWPE dense films described in Examples 1, 2 and 4b. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] Detailed Description Definitions and Terminology The present disclosure is not to be construed in a limiting sense, and for example, the terms used in this application should be interpreted broadly with respect to the meaning that one of ordinary skill in the art would ascribe to such terms.
[0038] With respect to imprecise terms, the terms "about" and "approximately" can be used interchangeably to refer to measurements that include the stated measurement and also include measurements that are reasonably close to the stated measurement. Measurements that are reasonably close to the stated measurement deviate from the stated measurement by a reasonably small amount, as understood and readily ascertained by one of ordinary skill in the relevant art. Such deviations can be due, for example, to measurement errors, differences in calibration of measuring and / or manufacturing equipment, human errors in reading and / or setting measurements, small adjustments made to optimize performance and / or structural parameters to account for differences in measurements associated with other components, specific implementation scenarios, imprecise adjustment and / or manipulation of objects by humans or machines, and / or the like. In cases where it is determined that the value of such reasonably small differences cannot be readily ascertained by one of ordinary skill in the relevant art, the terms "about" and "approximately" can be understood to mean + or -10% of the stated value.
[0039] Description of Various Embodiments Those skilled in the art will readily appreciate that the various aspects of the present disclosure may be implemented by any number of methods and devices configured to perform the intended functions. It should also be noted that the accompanying drawings referred to herein are not necessarily drawn to scale and may be exaggerated to illustrate various aspects of the present disclosure, and in that regard, the drawings should not be construed as limiting.
[0040] The present disclosure relates to high density ultra-high molecular weight polyethylene (UHMWPE) films, articles and composites containing these films, and methods for producing high density UHMWPE articles by paste processing of UHMWPE polymer to produce tapes or membranes which are then subjected to suitable processing conditions (e.g., heat compression or biaxial stretching, or heat compression in combination with biaxial stretching) to form high density films.
[0041] The UHMWPE film may be formed from an ultra high molecular weight polyethylene polymer having an average molecular weight (Mw) of at least about 2,000,000 g / mol and a high degree of crystallinity. In exemplary embodiments, the UHMWPE polymer may have an average molecular weight ranging from about 2,000,000 g / mol to about 10,000,000 g / mol, from about 4,000,000 g / mol to about 10,000,000 g / mol, from about 4,000,000 g / mol to about 8,000,000 g / mol, or any other range of average molecular weights included within these endpoints.
[0042] The UHMWPE polymer can have a high degree of crystallinity. The degree of crystallinity of the UHMWPE polymer can be measured by differential scanning calorimetry (DSC). As used herein, the phrase "highly crystalline" or "highly crystalline" is intended to refer to a UHMWPE polymer having a first enthalpy of melting greater than 190 J / g as measured by DSC. In another embodiment, the UHMWPE polymer has a first enthalpy of melting greater than 195 J / g, 200 J / g, 205 J / g, 210 J / g, 215 J / g, 220 J / g, 225 J / g, or 230 J / g.
[0043] Furthermore, the UHMWPE polymer can be a homopolymer of ethylene or a copolymer of ethylene and at least one comonomer. Suitable comonomers that can be used to form the UHMWPE copolymer include, but are not limited to, alpha-olefins or cyclic olefins having 3 to 20 carbon atoms. Non-limiting examples of suitable comonomers include 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, cyclohexene, and dienes having 20 or fewer carbon atoms (e.g., butadiene or 1,4-hexadiene). The comonomer can be present in the UHMWPE copolymer in an amount ranging from about 0.001 mol % to about 10 mol %, from about 0.01 mol % to about 5 mol %, from about 0.1 mol % to about 1 mol %, or any other amount included within these endpoints.
[0044] Additionally, the UHMWPE film may have a first endotherm associated with the UHMWPE polymer used at about 135°C to about 143°C. It should be noted that the terms "melting temperature", "melting temperature" and "melting point" may be used interchangeably herein. In at least one exemplary embodiment, the UHMWPE polymer has a melting point of approximately 140°C. Subsequent remelting of the UHMWPE polymer occurs at a temperature of about 127°C to about 137°C.
[0045] As mentioned above, UHMWPE polymer particles are first mixed with a suitable lubricant (e.g., isoparaffinic hydrocarbon) according to the general method described in U.S. Pat. No. 9,926,416 B2. The lubricated polymer particles are then processed into a tape in which a fibril structure is present (i.e., fibrils are present). The tape can be dried (to remove the lubricant) before forming a high density UHMWPE film using heat compression, biaxial stretching, or a combination thereof. The densification conditions can be controlled to retain a detectable DSC endothermic peak indicating the presence of residual fibril structure. Additionally, the UHMWPE film can have an endotherm at about 145° C. to about 155° C., or about 150° C., associated with fibrils within the film. Differential scanning calorimetry (DSC) can be used to identify the melting temperature (crystalline phase) of the UHMWPE polymer. This peak (or endotherm) at approximately 150° C. indicates the presence of fibrils within the high density UHMWPE film. 2-4 show DSC thermograms of UHMWPE films according to the present invention, showing two distinct peaks. It should be understood that the endothermic peak at about 150° C. is not present in conventionally processed UHMWPE porous membranes, tapes or films.
[0046] The high density UHMWPE films provided herein can have excellent optical properties. For example, the films can have a total light transmittance of at least about 90%, at least about 92%, at least about 94%, at least about 96%, or at least about 98%, measured from 360 nm to 780 nm. In some exemplary embodiments, the films can have a total light transmittance of about 90% to about 98%, measured from 360 nm to 780 nm, or any light transmittance between these endpoints.
[0047] Similarly, the high density films can have an average haze of less than 5%, less than 4%, less than 3%, less than 2%, or less than 1% measured from 360 nm to 780 nm. In some exemplary embodiments, the films can have an average haze of about 1% to about 5%, or any average haze between these endpoints, measured from 360 nm to 780 nm.
[0048] High density films formed from UHMWPE polymers can have a machine direction (MD) matrix tensile strength (MTS) of at least about 100 MPa, at least about 200 MPa, at least about 300 MPa, at least about 400 MPa, at least about 600 MPa, or at least about 800 MPa. In exemplary embodiments, the membranes can have a machine direction matrix tensile strength of from about 200 MPa to about 800 MPa, from about 400 MPa to about 800 MPa, or from about 600 MPa to about 800 MPa.
[0049] High density UHMWPE films have a matrix tensile strength (MTS) in the transverse direction (TD) of at least about 100 MPa, at least about 200 MPa, at least about 400 MPa, at least about 500 MPa, at least about 600 MPa, or at least about 800 MPa. In exemplary embodiments, the films have a matrix tensile strength in the transverse direction of from about 400 MPa to about 800 MPa, or from about 400 MPa to about 600 MPa.
[0050] High density UHMWPE films have an average matrix tensile strength ratio, measured in MD:TD, of from about 1:5 to about 5:1, from about 1:3 to about 3:1, or from about 1:2 to about 2:1.
[0051] High density UHMWPE films according to one embodiment of the invention can be utilized as barrier films or membranes that exhibit low CO, O, or N permeability. For example, high density UHMWPE films have a CO permeability of less than 10.0 barrels, less than 5 barrels, less than 1.0 barrels, or less than 0.1, where 1.0 barrel is 3.35×10-16 mole m / (s m 2 ·Pa). Similarly, the high density UHMWPE film can have an N2 permeability of less than 10.0 barrels, less than 5.0 barrels, less than 1.0 barrels, less than 0.1, or less than 0.05 barrels. Furthermore, the high density UHMWPE film can have an O2 permeability of less than 10.0 barrels, less than 5.0 barrels, less than 1.0 barrels, less than 0.1, or less than 0.01 barrels. It is understood that the CO2, O2, or N2 permeability is within any range formed from the above values, for example, the high density film can have a CO2, O2, or N2 permeability of 0.01 to 10 barrels, 0.1 to 8 barrels, or 0.1 to 6 barrels.
[0052] The high density UHMWPE film according to the embodiment of the present invention has a density of 0.01 to 1 g-mm / m 2 / day, 0.01~0.5g-mm / m 2 / day, or 0.01 to 0.25 g-mm / m 2 It can have a water vapor permeability of 100 / day.
[0053] High density films formed from UHMWPE polymers can have an average thickness of less than about 1 mm, less than about 0.1 mm, less than about 0.01 mm, less than about 0.001 mm, or less than 0.0005 mm. In exemplary embodiments, the high density films can have a thickness of about 0.0005 to about 1 mm, about 0.001 to about 1 mm, about 0.001 to about 0.1 mm, about 0.001 to about 0.01 mm, or any thickness within these ranges.
[0054] The present disclosure further relates to articles and composites comprising high density UHMWPE films. The articles can be in the form of films, fibers, tubes, or three-dimensional free-standing structures. In an exemplary embodiment, the articles are films. The composites can have two or more layers. The composites can include multiple layers of the high density UHMWPE films of the present invention, or can include one or more other polymer layers (e.g., high density plastic sheets, woven fabrics, nonwoven fabrics, electrospun membranes, or other porous membranes) that can be porous and non-porous, made from materials including, but not limited to, high density polyethylene (HDPE), UHMWPE, polyester, polyurethane, fluoropolymers, polytetrafluoroethylene, polypropylene, glass fiber, and any combination thereof.
[0055] The UHMWPE resin can be provided in particulate form, for example in the form of a powder. The UHMWPE powder can be formed from individual particles having a particle size of less than about 100 nm. Typically, the powder is provided as clusters of particles having a size of about 5 to about 250 microns, or about 10 to about 200 microns. In an exemplary embodiment, the clusters can have a size as small as possible, up to and including individual particles.
[0056] The UHMWPE films described herein can be produced by at least the following methods: (1) tape compression followed by stretching at about 140°C to about 170°C or about 150°C to about 160°C above the melting temperature of the UHMWPE polymer, (2) expanding the porous dry tape without compression at about 140°C to about 170°C or about 150°C to about 160°C above the melting temperature of the UHMWPE polymer, and (3) compressing the porous UHWPE membrane at about 140°C to about 170°C or about 150°C to about 160°C above the melting temperature of the UHMWPE polymer, or in combination with expansion at about 140°C to about 170°C or about 150°C to about 160°C above the melting temperature of the UHMWPE polymer.
[0057] In a method beyond tape compression and melt expansion, a high density UHMWPE film can be produced from UHMWPE polymer by forming a lubricated wet tape and drying the wet tape to form a dried porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g. The dried porous UHMWPE tape is compressed at a temperature below the melting temperature of the UHMWPE polymer, about 120°C to about 135°C or about 125°C to about 130°C, to form a high density UHMWPE tape. The high density tape is then stretched at a temperature above the melting temperature of the UHMWPE polymer, about 140°C to about 170°C or about 150°C to about 160°C.
[0058] To form a dry porous UHMWPE tape from the UHMWPE polymer, a paste is prepared containing the UHMWPE polymer as a powder and a lubricant, the paste is then cast into a tape, and the lubricant is removed to form a dry porous UHMWPE tape.
[0059] To form a paste, the UHMWPE polymer as a powder is first mixed with a lubricant such as light mineral oil. Other suitable lubricants include aliphatic, aromatic, halogenated hydrocarbons, etc., selected according to flammability, evaporation rate, and economic considerations. It is understood that the term "lubricant" as used herein is intended to refer to a processing aid consisting of an incompressible fluid that is not a solvent for the polymer at the process conditions. The interaction of the fluid with the surface of the polymer is such that a homogenous mixture can be made. It should also be noted that the choice of lubricant is not particularly limited, and the choice of lubricant is primarily a matter of safety and convenience. The lubricant can be added to the UHMWPE polymer in a ratio of 1 ml / 100 g to about 100 ml / 100 g or about 10 ml / 100 g to about 70 ml / 100 g. In one embodiment, the lubricant is added and the mixture is maintained at a temperature below the melting temperature of the UHMWPE polymer for a time (i.e., residence time) sufficient to wet the interior of the polymer clusters with the lubricant. "Sufficient time" can be described as time sufficient for the particles to revert back to a free-flowing powder. In another embodiment, a lubricant is added and mixed with the UHMWPE polymer, and the mixture is free-flowing and does not require a residence time.
[0060] After the lubricant is uniformly distributed on the surface of the particles (e.g., after it has wetted the interior of the clusters), the mixture returns to a free-flowing, powder-like state. In an exemplary embodiment, the mixture is heated to a temperature below the melting temperature of the UHMWPE polymer or the boiling point of the lubricant, whichever is lower. It should be understood that various times and temperatures can be used to wet the polymer, as long as there is enough time for the lubricant to adequately wet the interior of the clusters.
[0061] Once lubricated, the paste can be processed into a solid shape or preform without exceeding the melting temperature of the polymer. In an exemplary embodiment, the preform can be a fiber, tube, tape, sheet, or a three-dimensional free-standing structure. The lubricated particles are heated to a temperature below the melting temperature of the polymer and subjected to sufficient pressure and shear to form connections between the particles and create a solid shape. Non-limiting examples of methods for applying pressure and shear include ram extrusion, typically paste extrusion, or paste processing when a lubricant is present, and optionally calendering.
[0062] In an exemplary embodiment, the lubricated UHMWPE polymer is calendered to produce a cohesive flexible tape. As used herein, the term "cohesive" is intended to describe a tape that is strong enough for further processing. Calendering is performed at about 115°C to about 135°C, or about 125°C to about 130°C. The tape formed is of indefinite length and less than about 1 mm thick. The tape can be formed to have a thickness of about 0.01 mm to about 1 mm, about 0.08 mm to about 0.5 mm, or 0.05 mm to 0.2 mm or even thinner. In an exemplary embodiment, the tape is about 0.05 mm to about 0.2 mm thick.
[0063] In the next step, the lubricant can be removed to form a dry porous tape. In the example where mineral oil is used as the lubricant, the lubricant can be removed by washing the tape in hexane or other suitable solvent. The washing solvent is selected to have good solubility for the lubricant and to be sufficiently volatile to be removed below the melting point of the resin. If the lubricant has sufficient volatility, the lubricant can be removed without a washing step, or it can be removed by heat and / or vacuum. The tape is then dried, if necessary, typically by air drying. However, any conventional drying method can be used as long as the heating temperature of the sample is below the melting point of the UHMWPE polymer.
[0064] The dried porous UHMWPE tape or high density UHMWPE film can be cut to a size suitable for expansion and then stretched in at least two directions at a temperature above the melting temperature of the UHMWPE polymer, from about 140° C. to about 170° C., or from about 150° C. to about 160° C., to form a high density UHMWPE film, where the high density UHMWPE film has a first detectable endotherm of from about 135° C. to about 143° C. and a second detectable endotherm of from about 145° C. to about 155° C. The stretching can be performed at a rate of 20,000% / sec, or from about 0.1% to 20,000% / sec.
[0065] In another alternative, a high density UHMWPE film can be formed without compression by forming a porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mole and a melting enthalpy of at least 190 J / g.
[0066] The porous UHMWPE tape can then be stretched at a temperature above the melting temperature of the porous UHMWPE tape, from about 140°C to about 170°C, or from about 150°C to about 160°C, to form a high density UHMWPE film with a first detectable endotherm at about 135°C to about 143°C and a second detectable endotherm at about 145°C to about 155°C.
[0067] In yet another alternative, a dense UHMWPE film can be formed by compressing a porous UHMWPE membrane, with or without subsequent stretching at a temperature above the melting temperature of the UHMWPE polymer. The porous UHMWPE membrane can be formed as described in U.S. Pat. No. 9,926,416 (B2).
[0068] In another embodiment, the porous UHMWPE tape can be stretched at a temperature below the melting temperature of the porous UHMWPE tape, from about 100° C. to about 135° C., or from about 120° C. to about 130° C., and then or simultaneously compressed at a pressure of at least 1 MPa, thereby forming a high density UHMWPE film with a first detectable endotherm at about 135° C. to about 143° C. and a second detectable endotherm at about 145° C. to about 155° C. This high density film can be combined with stretching at a temperature above the melting temperature of the UHMWPE polymer, from about 140° C. to about 170° C., or from about 150° C. to about 160° C.
[0069] Stretching can be done at rates up to 20,000% / sec, or from about 0.1% to 20,000% / sec, either uniaxially or biaxially.
[0070] The high density UHMWPE film obtained by the above method exhibits excellent mechanical properties and optional properties such as high strength, optical uniformity, low haze, transparency, etc.
[0071] Test Method Although particular methods and apparatus are described below, other methods or apparatus as would be deemed suitable by one skilled in the art could be substituted.
[0072] Contact thickness measurement Thickness was measured by placing the sample flat on a granite block and using a manual Mitutoyo thickness gauge with a 6.35 mm metal plate (Mitutoyo Corporation, Kawasaki, Japan).
[0073] Mass per area measurement Mass per area measurements were made by weighing the dogbone samples used for mechanical characterization and dividing this mass (in grams) by the known area of the dogbone (in square meters).
[0074] DSC measurement DSC data were collected using a TA Instruments Discovery DSC over the temperature range of -50 °C to 200 °C at a heating rate of 10 °C / min. For resin samples, approximately 5 mg of powder was placed into a standard pan and lid combination available from TA Instruments. Membrane samples were prepared by punching 4 mm disks. The 4 mm disks were placed flat in the pan and the lid was folded down to sandwich the membrane disk between the pan and lid. A linear integration scheme from 80 °C to 180 °C was used to integrate the melting enthalpy data. Subsequent deconvolution of the melting region was performed using SeaSolve Software's PeakFit software (PeakFit v4.12 for Windows, Copyright 2003, SeaSolve Software Inc.). Standard conditions were used to fit the baseline (after inverting the data to generate the "positive" peak) and the observed data were then resolved into individual melting components.
[0075] Tensile testing and calculation of matrix tensile strength (MTS), modulus and toughness Tensile tests were performed in the machine direction (MD) and transverse direction (TD) using an Instron® Universal Tensile Tester (Instron Corporation, Norwood, Massachusetts, USA). ASTM D638-V dogbone tensile specimens were clamped in grips spaced 25 mm apart and tests were performed at a crosshead displacement rate of 1.27 mm / sec. Matrix tensile strength (MTS) is used to represent the tensile strength of highly porous articles and is calculated using the following formula:
number
[0076] The elastic modulus was calculated as the maximum slope plotted over five consecutive points of the stress versus strain plot after a load was detected during the test.
[0077] Toughness was calculated by integrating the area under the stress versus strain plot.
[0078] Gas permeability measurement Permeability was measured using a Lab Think Perme VacV2 permeability tester (Labthink International, Inc., Boston, MA) according to ASTM method D1434-82 (Standard Test Method for Determining Gas Permeability Properties of Plastic Films and Sheeting). Samples were tested by inserting the film into the tester, which allowed the permeability of various individual gases (CO 2 , N 2 and O 2 The measured gas permeability (GTR) is expressed as the permeability coefficient (cm 3 -cm / cm 2 -s-cmHg x 10 -10 or Barrers) and represents the velocity of gas through a volume of material of a given thickness at a given pressure.
[0079] Water vapor transmission rate measurement Measurements of the water vapor transmission rate of materials were performed according to ASTM method F-1249. The instrument used to test the water vapor transmission rate of materials was a MOCON Permatran W 3 / 34 (MOCON / Modern Controls, Inc., Minneapolis, MN). The permeant used was 100% RH water vapor (49.157 mmHg), the carrier gas was 100% nitrogen, dry, at atmospheric pressure, and the test was performed at 37.8°C. Samples were measured with a test area of approximately 0.1287 cm. 2 The specimen was cut to a size of 100 mm, masked, and fitted into the diffusion cell of the instrument and calibrated according to the MOCON Permatran W 3 / 34 instructions. The water vapor transmission rate or water vapor transmission rate was measured by the instrument in g / m 2The water vapor transmission coefficient for each sample was calculated by multiplying the water vapor transmission rate by the thickness of the test sample. The results are reported in g-mm / m 2 Reported per day.
[0080] Optical property measurement The total light transmittance and haze % were determined according to ASTM D1003-13 (Standard Test Method for Haze and Light Transmittance of Transparent Plastics). The incident light (T1), the total light transmitted through the sample (T2), the light scattered by the instrument (T3), and the light scattered by the instrument and the sample (T4) were measured in 1 nm steps over the wavelength range of 360-780 nm using a Jasco v-670 UV-Vis-NIR spectrophotometer (JASCO Deutschland GmbH, Pfungstadt, Germany) equipped with a Jasco iln-725 integrating sphere. The diffuse light transmittance (Td), total light transmittance (Tt) and haze % were calculated according to ASTM D1003-13. EXAMPLES
[0081] example The following examples were carried out on a laboratory scale, but it will be understood that they can be readily adapted to a continuous or semi-continuous process.
[0082] Example 1 powder preparation 300 g of ultra-high molecular weight polyethylene (UHMWPE) powder with a molecular weight of about 7,000,000 g / mol and a melting enthalpy of more than 190 J / g as measured by DSC (Mitsui Chemicals, Inc., manufactured as described in WO2012053261) was placed in a 2 liter screw cap jar. Figure 1 shows a typical DCS thermogram of the UHMWPE powder used. 180 mL of isoparaffinic hydrocarbon lubricant (ISOPAR™ V, ExxonMobil Chemical Company, Spring, Texas) was added and mixed at room temperature for 15 minutes at 30 rpm using a tumbler. The mixture was preheated to 60° C. prior to calendering.
[0083] Tape calendering Calender rolls, 20.3 cm diameter, with the gap between the rolls set at 0.2 mm, were preheated to 121°C. Lubricated polymer was introduced into the gap by a feeder to produce a continuous tape 15.2 cm wide at a line speed of 2.0 mpm. The tape was opaque, flexible, and approximately 0.21 mm thick.
[0084] Lubricant removal The tape was passed roll-to-roll through a large bath containing a low aromatic hydrocarbon solvent (ISOPAR™ G, ExxonMobil Chemical Company, Spring, TX) to replace the Isopar V™ with Isopar™ G, then dried at 50°C.
[0085] Heat compression After removing the lubricant, the dried tape was recalendered between 30.5 cm diameter rolls preheated to 130° C. at a line speed of 0.3 mpm with a roll gap set at 0.09 mm. The resulting compressed tape was translucent and flexible.
[0086] Biaxial stretching Samples were cut from the tape and placed into a Karo IV biaxial stretcher (available from Bruckner Group GmbH, Siegsdorf, Germany) and simultaneously stretched according to the following steps. 1. Preheat the sample to 145°C for 120 seconds. 2. At 145°C, 9.5 times at 37.5% / sec in the calendar direction and 9.5 times at 37.5% / sec in the transverse direction (perpendicular to the calendar direction)
[0087] A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the stretched high density UHMWPE film is included in Figure 2. The physical, mechanical, gas permeation, water vapor permeation and optical properties of Example 1 are shown in Figure 5 and Table 1.
[0088] Example 2 powder preparation Powder preparation was carried out according to the method described in Example 1.
[0089] Tape calendering Calender rolls, 30.5 cm diameter, with the gap between the rolls set at 0.16 mm, were preheated to 124°C. Lubricated polymer was introduced into the gap by a feeder to produce a continuous tape 15.2 cm wide at a line speed of 2.1 mpm. The tape was opaque, flexible, and approximately 0.17 mm thick.
[0090] Lubricant removal Lubricant removal was carried out according to the method described in Example 1.
[0091] Biaxial stretching: The samples were biaxially stretched as described in Example 1, but following the steps below. 1. Preheat the sample at 160°C for 30 seconds. 2. At 160°C, using constant speed mode, 2.5x at 28% / sec in the calender direction and 9.5x at 70% / sec in the transverse direction (perpendicular to the calender direction).
[0092] A differential scanning calorimetry (DSC) thermogram showing the two distinct melting points associated with the stretched high density UHMWPE film is included in Figure 3. The physical, mechanical and gas permeation properties of Example 2 are shown in Figure 5 and Table 1.
[0093] Example 3 Creation of porous membranes A porous polyethylene membrane was prepared according to US Pat. No. 9,926,416 (B2). The membrane had a mass per area of 14.7 g / m 2 , bubble point pressure 324kPa, ATEQ airflow 2.2cm 2 The membrane had an area of 1.2 m / s and a flow rate of 7 l / hr at 1.2 kPa, a calender MTS of 189 MPa and a transverse MTS of 183 MPa. This membrane was used in all subsequent processing.
[0094] Heat compression The membrane was cut, two layers were cross-laminated, and then placed on a steel autoclave plate between two layers of polymethylpentene film (TPX™, Mitsui Chemicals, Tokyo, Japan) and sealed with tape. Vacuum was applied to the sample, after which the temperature and pressure were increased over a period of 45 minutes. Two samples were made with different compression temperatures and subsequent processing.
[0095] Example 3a was prepared at a temperature of 155°C using a pressure of 1.7 MPa.
[0096] Example 3b was prepared at a temperature of 160° C. using a pressure of 1.7 MPa.
[0097] The resulting dense film was transparent with no detectable air flow. The DSC thermogram of Example 3a is shown in Figure 4, and the mechanical properties of Example 3a are shown in Table 1.
[0098] Example 4 The high density films formed as Examples 3a and 3b were further subjected to biaxial stretching. Biaxial stretching Sections of Examples 3a and 3b were cut and placed in a Karo IV biaxial stretcher as described in Example 1 and stretched according to these procedures. Example 4a a. Preheat the sample (example 3a) at 155°C for 30 seconds b. At 155°C, 3.0x at 3% / sec in the calendar direction and 3.0x at 3% / sec in the transverse direction 2. Example 4b a. Preheat the sample (example 3b) at 155°C for 30 seconds b. At 155°C, 2.0× at 3% / sec in the calendar direction and 2.0× at 3% / sec in the transverse direction.
[0099] Gas and water vapor transmission data for Example 4b are shown in FIG.
[0100] [Table 1]
[0101] The invention of this application has been described above both generally and with respect to specific embodiments. While the invention has been shown in what are believed to be preferred embodiments, a wide variety of alternatives known to those skilled in the art may be selected within the scope of the general disclosure. The invention is not otherwise limited, except as set forth in the claims below.
Claims
1. 1. A high density ultra-high molecular weight polyethylene (UHMWPE) film, A first endotherm at about 135° C. to about 143° C.; A second endotherm at about 145° C. to about 155° C., and A total light transmittance of at least about 90% measured from 360 nm to 780 nm 1. A high density ultra-high molecular weight polyethylene (UHMWPE) film comprising:
2. 2. The high density UHMWPE film of claim 1, wherein the UHMWPE film has a machine direction (MD) matrix tensile strength of at least 200 MPa.
3. 3. The high density UHMWPE film of claim 1 or claim 2, wherein the UHMWPE film has a matrix tensile strength in the transverse direction (TD) of at least 400 MPa.
4. The high density UHMWPE film according to any one of claims 1 to 3, wherein the ratio of matrix tensile strength MD:TD is from about 1:5 to about 5:
1.
5. The UHMWPE film is 2 Transparency, O 2 Permeability or N 2 The high density UHMWPE film according to any one of claims 1 to 4, having a permeability of less than 10 barrels.
6. The high density UHMWPE film according to any one of claims 1 to 5, wherein the UHMWPE film has a thickness of 0.0005 mm to 1 mm.
7. The high density UHMWPE film according to any one of claims 1 to 6, wherein the high density UHMWPE film is formed from a UHMWPE polymer having a molecular weight of about 2,000,000 g / mol to about 10,000,000 g / mol and a melting enthalpy of greater than 190 J / g.
8. A composite material comprising the high density UHMWPE film according to any one of claims 1 to 7.
9. An article comprising the high density UHMWPE film of any one of claims 1 to 8.
10. 1. A method for forming a high density UHMWPE film, comprising: forming a dry porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g; compressing the dried porous UHMWPE tape at a temperature below the melting temperature of the UHMWPE polymer; and stretching the UHMWPE tape in at least two directions at a temperature above the melting temperature of the UHMWPE polymer to form a high density UHMWPE film; The high density UHMWPE film comprises: A first detectable endotherm at about 135° C. to about 143° C.; and A detectable second endotherm at about 145° C. to about 155° C.; The method comprises:
11. The method of claim 10, wherein the high density UHMWPE film has a total light transmittance measured from 250 nm to 800 nm of at least about 98%.
12. The forming process includes: Providing a paste comprising a UHMWPE polymer as a powder and a lubricant; forming the paste into a tape; removing the lubricant to form a dry porous UHMWPE tape; and stretching the tape to form a high density UHMWPE film; 12. The method of claim 10 or 11, comprising:
13. The method according to any one of claims 10 to 12, wherein the step of stretching the compressed UHMWPE tape is carried out at a temperature of 140°C to 170°C and at a rate of about 0.1% to 20,000% / sec.
14. The high density UHMWPE film further has a ratio of machine direction matrix tensile strength to transverse direction matrix tensile strength of about 1:5 to about 5:1, a matrix tensile strength of at least 500 x 500 (MD x TD) MPa, and 2 , O 2 Or N 2 The permeability is 0.01 to 10 barrels, and the water vapor permeability coefficient is 0.02 g mm / m 2 The method according to any one of claims 10 to 13, wherein the daily intake is less than 100 mg / day.
15. 1. A method for forming a high density UHMWPE film, comprising: forming a dry porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g; and stretching the dried porous UHMWPE tape in at least two directions at a temperature above the melting temperature of the UHMWPE polymer to form a high density UHMWPE film; The high density UHMWPE film comprises: A first detectable endotherm at about 135° C. to about 143° C.; and A second detectable endotherm at about 145° C. to about 155° C.; A method comprising:
16. The forming process includes: Providing a paste comprising a UHMWPE polymer as a powder and a lubricant; forming the paste into a tape; removing the lubricant to form a dry porous UHMWPE tape; and stretching the tape to form a high density UHMWPE film; 16. The method of claim 15, comprising:
17. 17. The method of claim 15 or 16, wherein the step of stretching the dried UHMWPE tape is carried out at a temperature of 140°C to 170°C and at a rate of about 0.1% to 20,000% / sec.
18. The high density UHMWPE film further has a ratio of machine direction matrix tensile strength to transverse direction matrix tensile strength of about 1:5 to about 5:1, a matrix tensile strength of at least 200 x 200 (MD x TD) MPa, and 2 , O 2 Or N 2 The method of any one of claims 15 to 17, wherein the permeability is from 0.01 to 10 barrels.
19. 1. A method for forming a high density UHMWPE film, comprising: (a) forming a porous UHMWPE tape from a UHMWPE polymer having a molecular weight of at least 2,000,000 g / mol and a melting enthalpy of at least 190 J / g; (b) expanding the porous UHMWPE tape at a temperature below the melting temperature of the porous UHMWPE tape to form a porous membrane; and (c) compressing the porous UHMWPE membrane at a pressure of at least 1 MPa to form a dense UHMWPE film; The high density UHMWPE film comprises: A first endotherm at about 135° C. to about 143° C.; A second detectable endotherm at about 145° C. to about 155° C.; A method comprising:
20. 20. The method of claim 19, further comprising: (d) stretching the high density UHMWPE film at a temperature above the melting temperature of the UHMWPE polymer.
21. 21. The method of claim 19 or claim 20, wherein the stretching and compressing steps are performed simultaneously.
22. The method of any one of claims 19 to 21, wherein the stretching step after compression is carried out at a temperature of about 140°C to about 170°C.
23. The high density UHMWPE film further has a ratio of machine direction matrix tensile strength to transverse direction matrix tensile strength of about 1:5 to about 5:1, a matrix tensile strength of at least 200 x 200 (MD x TD) MPa, and a water vapor permeability of 0.21 g-mm / m 2 The method of any one of claims 19 to 22, wherein the daily dose is less than one day per day.
24. The method of any one of claims 10 to 23, wherein the stretching step comprises biaxial or radial stretching.
Citation Information
Patent Citations
Polyethylene resin film
JP1995165941A
Polyethylene article with improved resistance to water vapor transmission
JP1998511996A
Production of high-molecular weight polyolefin film having improved transparency
JP2000313070A
Medical device made from ultra-high molecular weight polyolefin
JP2003517891A
Method for producing porous articles derived from ultra-high molecular weight polyethylene
JP2016508535A
Cited By
Method for Producing Porous Articles from Ultra-High Molecular Weight Polyethylene
JP2025506187A
Method for producing porous articles from ultra-high molecular weight polyethylene
JP7793069B2
